INTERNAL TRANSCRIBED SPACER (ITS), AN IDEAL DNA BARCODE FOR SPECIES DISCRIMINATION IN CRAWFURDIA WALL. (GENTIANACEAE) - Zhang, Dequan; Jiang, Bei; Duan, Lizhen; Zhou, Nong (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: DNA barcoding is a technique used to identify species based on species-specific differences in short regions of their DNA. It is widely used in species discrimination of medicinal plants and traditional medicines. Materials and Methods: In the present study, four potential DNA barcodes, namely rbcL, matK, trnH-psbA and ITS (nuclear ribosomal internal transcribed spacer) were adopted for species discrimination in Crawfurdia Wall (Genetiaceae). Discriminatory ability of these DNA barcodes and combinations were evaluated using three classic methods (Distance, Blast and Tree-Building). Results: As a result, ITS, trnH-psbA and rbcL regions showed extremely great universality for a success rate of 100%; whereas matK was disappointing for which only 65% samples gained useful DNA sequences. ITS region performed very well in this study which could clearly and effectively identify the five species in Crawfurdia. On the contrary, trnH-psbA and rbcL were much weaker in discrimination among these species. Conclusion: ITS marker was an ideal DNA barcode in Crawfurdia and it should be incorporated into one of the core barcodes for seed plants.